2020
DOI: 10.1007/s12032-020-1346-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle isolation from human renal cancer tissue

Abstract: Renal cell carcinoma is a lethal disease that is often discovered incidentally. New non-invasive biomarkers are needed to aid diagnosis and treatment. Extracellular vesicles (EVs), membranous vesicles secreted by all cells, are a promising potential source for cancer biomarkers, but new methods are required that are both sensitive and specific for cancer identification. We have developed an EV isolation protocol optimized for kidney tumor and normal kidney tissue that yields a high vesicle concentration, confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Separated EVs were assessed by transmission electron microscopy (TEM) as described previously (Zieren et al., 2020). First, 10 μl of each sample was adsorbed to an ultra‐thin carbon coated 400 mesh copper grid that was glow discharged (EMS GloQube™) by floatation for 2 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Separated EVs were assessed by transmission electron microscopy (TEM) as described previously (Zieren et al., 2020). First, 10 μl of each sample was adsorbed to an ultra‐thin carbon coated 400 mesh copper grid that was glow discharged (EMS GloQube™) by floatation for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Nanoparticle tracking analysis (NTA) (NanoSight NS300, Malvern Pananalytical) was used to measure the particle counts and size distributions of EV preparations separated from different sample types using different methods, as described previously (Zieren et al., 2020). Briefly, 10 μl of each EV sample was diluted with PBS according to the detection range (20–100 particles/frame).…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are only few data on the isolation of exosomes from kidney tissue. Zieren et al reported the isolation of exosomes based on collagenase treatment, differential centrifugation, and filtration with 800 nm and 450 nm filters, followed by ultracentrifugation [46]. In contrast, our protocol was based on a density gradient without mechanical filters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the size, the source of exosomes plays an important role in the selection of the isolation method. Our isolation protocol was optimized in order to obtain the best possible ratio of purity and concentration while being cost-and time-efficient [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are secreted as the vesicles of a size range of 30 to 150 nm diameter, which are enclosed by the cell membrane. Inward budding of late endosomes develop into intracellular multivesicular endosomes and RNA, DNA, proteins and other small moleculars are encapsulated into exosomes during the formation of exosome [1,2]. Various types of cells such as immune cells, broblast and endothelial cells, release exosomes into the extracellular space and microenviroment, involving the tumor pathogenesis [3,4].…”
Section: Introductionmentioning
confidence: 99%